Leptomeningeal contrast enhancement and blood-CSF barrier dysfunction in aseptic meningitis. Issue 6 (December 2015) - Alonso, Angelika; Eisele, Philipp; Ebert, Anne D.; Griebe, Martin; Engelhardt, Britta; Szabo, Kristina; Hennerici, Michael G.; Gass, Achim
Abstract : Objective: To investigate the blood-CSF barrier (BCSFB) dysfunction in aseptic meningitis. Methods: In our case series of 14 patients with acute aseptic meningitis, we compared MRI characteristics with CSF findings. Results: Contrast enhancement in the sulcal space in a leptomeningeal pattern was visualized in 7 patients with BCSFB dysfunction categorized as moderate to severe as evidenced by the CSF/serum albumin ratio (Qalb ) but was not present in those with mild or no barrier disturbance ( p = 0.001). The Qalb as a marker for the leakiness of the BCSFB and, more indirectly, of the blood-brain barrier (BBB) was positively correlated with the incidence of leptomeningeal contrast enhancement seen on postcontrast fluid-attenuated inversion recovery (FLAIR) MRI ( p = 0.003). Patients with a more pronounced brain barrier dysfunction recovered more slowly and stayed longer in the hospital. Conclusions: The severity of meningeal BBB disturbance can be estimated on postcontrast FLAIR MRI, which may be of diagnostic value in patients with aseptic meningitis.